Stress analysis of mini compact manually operated crane design - Zainal Abidin, Nurrul Amilin; Fauzi, Muhammad Irsyad (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This project aims on designing a mini compact manually operated crane. This crane is designed to be easily maneuverable and can fit into tight spaces, making it ideal for tasks such as lifting tools, materials, or equipment in confined work areas. The design of mini compact crane is incorporating with features such as articulating arms and lever-operated model. A stress analysis is performed on the articulating arm to ensure that this manually operated crane can withstand the expected loads and forces it will experience during its extended use.